RECONSTRUCTING EQUITABLE SPECIAL AUTONOMY BASED ON LOCAL KEARIFICITY AND REGIONAL POTENTIALS - bambang (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The granting of special autonomy to local governments does not have a positive impact on its implementation, it can be seen that the regional governments that implement special autonomy are included in the category of underdeveloped and poor regions, this is due to the implementation that cannot be maximized and the limited authority to manage the potential and resources of the region and the authority of local governments to innovate is very limited and lacking due to most of the kunkuren authority is still under the authority of the government, so that the dependence on assistance from the central government is still large, thus a reconstruction of regulations on special autonomy is needed with the aim that it can be implemented and the regions are able to be independent in managing regional potential based on local resources and wisdom. The research aims to find out the problems of special autonomy and the concept of regulation which will be applied so that it has a positive impact in implementing special autonomy. The discussion uses a normative juridical approach method focused on analyzing literature and legal documents through doctrinal research. From the results of studies conducted in the implementation of special autonomy to several regional governments in Indonesia has not been successful and the main objectives of special autonomy have not been achieved, therefore it is necessary to change the concept of special autonomy regulation through the reconstruction of the legal concept of special autonomy in a form where concurrent authority only exists in local governments, special autonomy in the form of material autonomy whose authority lies with the provincial government and the central government has the authority to form regulations and implement regulations carried out by local governments, namely the provincial government